Application of Edge Computing in 5g Communications. Issue 1 (January 2020) - Wang, Tongyu
Abstract: As the next generation of the wireless communication technology, the fifth generation communication (5G) would bring revolutionary changes to our life. In this paper, we firstly give an introduction of the typical scenarios of 5G's applications. Then we review the basic concepts of new computing hypotheses including cloud computing, fog computing and in some extent even for edge computing. Combining with the demand of 5G's application, we analyze the opportunities and challenges of these new computing hypotheses in 5G era.